THE DEVELOPMENT OF ONLINE LEARNING GAME ON LINEAR PROGRAM COURSES - Zainnur Wijayanto; Dafid Slamet Setiana; Betty Kusumaningrum (Jurnal Infinity, 2022)
This study aims to produce online learning games on linear program subjects for 3rd-semester students that are valid, practical, efective and can increase student learning motivation. Students are less interested in linear program subject because it requires high analysis skill and feel boring. This research and development model consisting of the stages of define (literature study and field survey), design (early product design activities), develop (expert validation, product revisions, and development testing), and disseminate (final product revision) with descriptive analysis techniques qualitatively and quantitatively. Qualitative descriptive analysis techniques are used to describe the stages of development that describe the results of observations of the implementation and effectiveness of online learning games that have been developed in the field. Quantitative descriptive analysis techniques are used at the development stages. This study has achieved the expected goal: producing online learning games for linear program subjects that are valid (very good category), practical (very good category), and effective (85.71% of students had achieve a minimum score of C).